2020
DOI: 10.3390/ijerph17103692
|View full text |Cite
|
Sign up to set email alerts
|

Representation of CYP3A4, CYP3A5 and UGT1A4 Polymorphisms within Croatian Breast Cancer Patients’ Population

Abstract: Single nucleotide polymorphism (SNP) in genes encoding drug-metabolizing enzymes (DME) could have a critical role in individual responses to anastrozole. Frequency of CYP3A4*1B, CYP3A5*3 and UGT1A4*2 SNPs in 126 Croatian breast cancer (BC) patients and possible association with anastrozole-induced undesirable side effects were analyzed. Eighty-two postmenopausal patients with estrogen receptor (ER)-positive BC treated with anastrozole and 44 postmenopausal ER-positive BC patients before hormonal adjuvant thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…No ADRs have been associated with other SNPs (rs4646, rs10046, rs727479, rs1062033) [141]. The CYP3A4*1B, CYP3A5*3 and UGT1A4*2 variants may influence the onset of ADRs in women with estrogen receptor (ER)-positive breast cancer treated with anastrozole [142].…”
Section: Cancermentioning
confidence: 99%
“…No ADRs have been associated with other SNPs (rs4646, rs10046, rs727479, rs1062033) [141]. The CYP3A4*1B, CYP3A5*3 and UGT1A4*2 variants may influence the onset of ADRs in women with estrogen receptor (ER)-positive breast cancer treated with anastrozole [142].…”
Section: Cancermentioning
confidence: 99%
“…Our study revealed strong LD between CYP3A4*1.001 and CYP3A5*1 [4,24], CYP3A4*1.001 and CYP3A5*3 [25][26][27], or CYP3A4*22 and CYP3A5*3. However, the effect of CYP3A4*1.001 is not influenced by CYP3A5, C0/D being significantly reduced in CYP35, independently of the CYP3A4 variant [18,28].…”
Section: Discussionmentioning
confidence: 48%
“…However, individuals homozygous for UGT1A4 48 Val had significantly lower mean concentrations of 4-OH-TAM-O-Gluc and endoxifen-Gluc than wt/wt plus wt/48Val subjects. Low activity of trans-4-hydroxytamoxifen glucuronidation was also observed in carriers of the UGT1A4 24Thr/48Leu allele [4,8,18].…”
Section: Results Discussionmentioning
confidence: 85%
“…UGT2B7 demonstrated the highest affinity and activity for trans-4-hydroxytamoxifen [ 26,16,30]. The UGT1A4 gene encodes an enzyme that catalyzes the formation of a glucuronide bound by quaternary ammonium to TAM [4,7,8,18]. Two unlinked m issense polymorphisms were identified in this gene: in codon 24 Pro>Thr (rs6755571) and in codon 48 Leu>Val (rs2011425).…”
Section: Results Discussionmentioning
confidence: 99%